Evaluasi Tatakelola Pembangunan Jembatan Wae Racang Di Kabupaten Manggarai Provinsi NTT - Gon, Kasmir (UNIVERSITAS MALIKUSSALEH, 2024)
The Wae Racang Bridge is a node for Road Sections: Golowoi-Meda, Beo Kina-Pau-Wae Racang and Muwur-Bapa-Wae Racang. The bridge was built on the Wae Racang River which is the boundary between West Cibal District and North Rahong, which was built in 2014 and hasnt been used at all by infrastructure users until April 2023. This study aims to find out the causes of the unutilized bridge based on public perceptions and to evaluate the management of regional infrastructure. The research was carried out in several stages, including review of related journal articles, observation of research locations, observations of the PUPR Office as the organizer of the work, surveys of community perceptions, simple statistical data processing to find out the dominant response, discussion, and conclusions. Of the 43 respondents, the dominant response stated that the budget planning wasnt based on a feasibility study on economic feasibility studies, resulting in the Wae Racang Bridge being built not bringing economic benefits to the community, so that the development budget became redundant which describes the performance and management of local regional administrations in the matter of transportation infrastructure development still needs to be improved because it doesnt consider sustainability aspects at all. bridge construction.